Efektifitas terapi musik klasik terhadap penurunan tingkat halusinasi pada pasien halusinasi dengar Di rsj tampan provinsi riau - Rafina - Damayanti; Jumaini - -; Sri - Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine effectiveness of classical music therapy toward decrease level hallucination in patient with auditory of hallucination at RSJ Tampan Riau province. The research used quasy experimental design with pretest-posttest design with control group which divided into experimental group and control group. Sample of this research is 34 people devided into 17 people as the exsperimental group and 17 people as a control group with using purposive sampling of techniques sampling. Instruments of this research has been tested the validity and reability. The experimental group were given interventions with music therapy of five time in five days for 10-15 minutes. Then the data analyzed into univariate and bivariate using wilcoxon test and mean-whitney test. The result of the research showed there is significantly to contrast level of hallucination after given intervention between experimental group and control group with p value 0,000 (<0,05). In conclusion level of hallucination experimental group was lower than control group after given intervention. The result is expected of music therapy to be one nursing intervention to decrease level hallucination with auditory of hallucination. Key words: Patients with hallucination, music therapy, level of auditory hallucination.